Reversible Severe Acute Lactic Acidosis Caused by Thiamine Deficiency in Intensive Care Unit - Jisu Hong; Daehong Cho; Hong Jun Kim; Jaemin Jo; Gil Myeong Seong (Case Reports in Critical Care)
Lactic acidosis is a common cause of metabolic acidosis in hospitalized patients. It is typically caused by hypoperfusion and anaerobic metabolism and is often associated with sepsis. However, it can also result from impaired lactate metabolism, independent of hypoxemia. We report the case of a 50-year-old woman with severe lactic acidosis who was admitted to the intensive care unit. Lactic acidosis was initially attributed to an uncontrolled infection. However, brain magnetic resonance imaging revealed Wernicke’s encephalopathy due to thiamine deficiency. The administration of high-dose intravenous thiamine rapidly improved the mental status and normalized serum lactate levels. This case highlights the importance of identifying thiamine deficiency as a reversible cause of lactic acidosis in critically ill patients.